2017
DOI: 10.9790/0990-0502016877
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Prospect of Nigeria’s Gongola Basin Based on Gravity Data Interpretation

Abstract: With an upbeat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Structural lineaments distribution, distribution density, and interconnectivity play a significant role in providing a passage through which hot molten rock material (magma) found within the deeper parts of the crusts are transported to the Earth's surface [31]. Therefore, this process enables heat transmission from the magma chamber to the earth's surface via the convection process [44].…”
Section: Structural Lineaments Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural lineaments distribution, distribution density, and interconnectivity play a significant role in providing a passage through which hot molten rock material (magma) found within the deeper parts of the crusts are transported to the Earth's surface [31]. Therefore, this process enables heat transmission from the magma chamber to the earth's surface via the convection process [44].…”
Section: Structural Lineaments Mappingmentioning
confidence: 99%
“…The study revealed the presence of NE-SW and NW-SE structural trends. Bassey et al [31] conducted an interpretation of gravity data over the same Gongola basin with the aim of understanding the hydrocarbon prospectivity of the area. the study established the structural configurations as well as revealed the areas of greater sediments thickness that could serves as an area of better prospectivity.…”
Section: Introductionmentioning
confidence: 99%